Gender difference in the associations between health literacy and problematic mobile phone use in Chinese middle school students - Dan-Lin Li; Sizhe Wang; Daoxu Zhang; Rong Yang; Jie Hu; Yanni Xue; Xuexue Huang; Yuhui Wan; Chen-Wei Pan; Jun Fang; Shichen Zhang (BMC, 2023)
Abstract Background Problematic mobile phone use (PMPU) is becoming increasingly popular and has serious harmful effects on physical and mental health among adolescents. Inadequate health literacy (HL) is related to some risky behaviors and mental health problems in adolescents. Nevertheless, few studies have explored the relationship between HL and PMPU and the gender difference in the relationship among Chinese adolescents. The aim of this study was to examine the associations between HL and PMPU and explore gender difference in the associations. Methods A total of 22,628 junior and senior high school students (10,990 males and 11,638 females) in 6 regions of China participated in this study. HL and PMPU were measured by self-report validated questionnaires. Chi-square tests and logistic regression analysis were conducted in the study. Results Logistic regression analysis showed that students with inadequate HL are likely to have PMPU (OR = 2.013, 95% CI: 1.840-2.202), and different degrees of association can be seen in six dimensions. Besides, in both males and females, students with inadequate HL had a higher risk of PMPU (OR male = 1.607, 95% CI: 1.428-1.807; OR female = 2.602, 95% CI: 2.261-2.994). Regarding the gender difference, the results showed that males had more PMPU than females, and the difference was more significant for students with adequate HL than those with inadequate HL (OR inadequate = 1.085, 95% CI: 1.016-1.159; OR adequate = 1.770, 95% CI: 1.490-2.101). Similarly, there were associations in the six dimensions. Conclusions HL decreases PMPU, and males have a higher risk of PMPU than females. These findings suggest a reasonable strategy to reduce PMPU by improving the HL level of adolescents.